2020
DOI: 10.3390/en13010194
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Electricity Demand by Personal Light Electric Vehicles (PLEVs): An Example of e-Motor Scooters in the Context of Large City Management in Poland

Abstract: Personal light electric vehicles (PLEVs) are a phenomenon that can currently be observed in cities, intended to be an ecological form of transport. The authors of the paper make an attempt to determine electricity consumption by PLEVs in the context of managing a large city in accordance with the concept of sustainable development. The article is of a cognitive nature. Research questions posed against the background of the goal formulated are as follows: how strong will the demand for PLEVs be (in the example … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Going further, it is also worth mentioning the thematic focus of the publication, related to the attempt to determine the number of electric vehicles (incl. buses) in different countries [2,3] or an attempt to estimate the amount of energy consumed by electric vehicles [4]. An interesting perspective is also the analysis in terms of identifying opportunities for the development of the described technology in various countries and regions of the world [4,5] or the directions of further research on electric vehicles and their impact on the environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Going further, it is also worth mentioning the thematic focus of the publication, related to the attempt to determine the number of electric vehicles (incl. buses) in different countries [2,3] or an attempt to estimate the amount of energy consumed by electric vehicles [4]. An interesting perspective is also the analysis in terms of identifying opportunities for the development of the described technology in various countries and regions of the world [4,5] or the directions of further research on electric vehicles and their impact on the environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 10, Martínez-Navarro et al (2020) estimated e-scooters' energy consumption to be 0.012 kWh/km, Brdulak et al (2020) reported it to be 0.04 kWh/km, and Agora Verkehrswende (2019) reported it to be 0.01 kWh/km [29,34,36]. Plainly, the numbers by themselves do not mean anything; it is necessary to associate them with other comparable variables to reach a conclusion.…”
Section: Impacts On Energy Consumptionmentioning
confidence: 99%
“…Based on the Bird e-scooter, with 1 kW/h of energy, e-scooters can travel approximately 100 km, whereas an electric car can travel 6 km [29]. According to Brdulak et al (2020), who made an assumption based on data from rental companies in Poland, an e-scooter can travel 100 km with 4 kWh energy [36]. According to Wired (2018), e-micromobility vehicles are 20 times more efficient than electric vehicles and 102 times more efficient than conventional fossil fuel vehicles; furthermore, e-scooters cover their cost in just 4 months and are seen as the most cost-effective vehicles for short distances compared to other transportation modes [31].…”
Section: Impacts On Energy Consumptionmentioning
confidence: 99%
“…Such a situation is an important starting point for all activities, from legislative and formal solutions, to social campaigns raising awareness of the need for changes. In the case of economic analyses, purely financial factors are taken into account in the first place, although issues of a worldview nature, which reflect changing trends and consumer behavior, are also not without significance (Brdulak et al 2020;Drożdż et al 2020). The data contained in the "Polish EV Outlook 2020" report of the Polish Alternative Fuels Association (PSPA) of April 29, 2020 was adopted as the source for the development of profitability estimates for the implementation (PSPA 2020b).…”
Section: Changes In Transport As a Response To Environmental Challengesmentioning
confidence: 99%